2007
DOI: 10.1021/jo0705925
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Crystallization-Induced Diastereomeric Transformation Based on a Reversible Carbon−Sulfur Bond Formation. Application to the Synthesis of a γ-Secretase Inhibitor

Abstract: This paper describes a remarkably efficient process for the preparation of gamma-secretase inhibitor 1. The target is synthesized in only five steps with an overall yield of 58%. The key operation is a highly selective and practical, crystallization-driven transformation for the conversion of a mixture of tertiary benzylic alcohols into the desired sulfide diastereomer with 94:6 dr. This unprecedented process is based upon a reversible carbon-sulfur bond formation under acidic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A Merck group described a CIDT based on a reversible formation of carbon‐sulfur bonds (Scheme 29). [81] They found out that epimeric mixture of carbinols epi ‐ 76 readily dehydrated if dissolved in MeSO 3 H and upon addition of a slight excess of thiol 77 provided cis / trans ‐ 78 in ca 1:1 dr. Fortunately, the desired cis ‐stereoisomer had a higher mp than trans ‐ 78 (144 versus 127 °C) and was less soluble in the used solvent system. Addition of water in a rather narrow volumetric window (9–13 vol%) was determined to be critical for optimal rate and yields of CIDT.…”
Section: Examples Of Cidtmentioning
confidence: 99%
“…A Merck group described a CIDT based on a reversible formation of carbon‐sulfur bonds (Scheme 29). [81] They found out that epimeric mixture of carbinols epi ‐ 76 readily dehydrated if dissolved in MeSO 3 H and upon addition of a slight excess of thiol 77 provided cis / trans ‐ 78 in ca 1:1 dr. Fortunately, the desired cis ‐stereoisomer had a higher mp than trans ‐ 78 (144 versus 127 °C) and was less soluble in the used solvent system. Addition of water in a rather narrow volumetric window (9–13 vol%) was determined to be critical for optimal rate and yields of CIDT.…”
Section: Examples Of Cidtmentioning
confidence: 99%
“…Davies showed that Grignard reagents can be added to the ketones of ketoacids if the acids are first converted to their magnesium salts by treatment with Et 3 N and MgCl 2 in THF, followed by filtration of Et 3 N·HCl . Accordingly, treatment of acid 17 with MgCl 2 and Et 3 N furnished carboxylate 18 , which was treated with 9 .…”
Section: The Coupling Stepmentioning
confidence: 99%
“…During the course of a recent research program, we required a concise and selective method to access 4-substituted cyclohexyl aryl ester 1 . Although 1,4 disubstituted cyclohexane derivatives are achiral due to the presence of a C 2 -symmetry element, the selective preparation of either of the two possible achiral diastereomers represents a significant synthetic challenge …”
mentioning
confidence: 99%